Manajemen Komplikasi dan Keluhan pada Pasien yang Menjalani Hemodialisis - Devia Putri Lenggogeni; Hema Malini; Boby Febri Krisdianto (Warta Pengabdian Andalas, 2020)
Hemodialysis is one of the renal replacement therapies used by many patients with terminal renal failure. Hemodialysis is an effective renal replacement therapy and is the most commonly used in managing terminal renal failure. However, hemodialysis is a complicated and uncomfortable therapy with several complications. Hemodialysis complications need to be prevented and controlled so that the patient's life remains optimal, and the worse condition does not occur. This program provides knowledge and information to patients undergoing hemodialysis. It used to handle complications and problems caused by terminal renal failure and hemodialysis. This program is an education program to 32 patients undergoing hemodialysis at the hemodialysis unit RSUP. Dr. M. Djamil Padang. The program was carried out by using videos and giving booklet to patients. It showed an increase in patient's knowledge to manage complications and problems caused by hemodialysis. It provides information related to the management of complications and problems in patients undergoing hemodialysis, which can be done by the patient. It is aimed at patients to improve skills in managing complications and problems caused by hemodialysis.